DIETARY SALT INTAKE: HISTORY, ASSESSMENT, AND BENEFIT IN HYPERTENSIVE TREATMENT - Raj, Sunitha Esther; Tan, Lee Mei; Md Redzuan, Adyani (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Multiple lines of investigation including genetic, epidemiological, and interventional studies have demonstrated consistently a positive relationship between salt intake, blood pressure (BP) increment, and cardiovascular consequences. In addition, it has been documented that excessive salt intake can be attributed to various health complications such as asthma, osteoporosis, obesity, and gastric cancer. On the contrary, a reduction in salt intake has been shown to reduce BP and improve health outcomes, although the evidence is not completely unequivocal. Despite this discrepancy, a lowsodium diet is widely being recommended to all hypertensive patients in particular, as evidence against its efficacy in conjunction with optimum hypertensive treatment is well established. Determination of salt intake among hypertensive patients is important since dietary salt restriction had been proven to improve BP control in conjunction with optimum pharmacological management. Various methods have been used to estimate sodium intake includes 24-hrs urinary sodium, overnight urinary sodium, spot urinary sodium/creatinine ratio, and dietary survey methods. Reducing population salt intake has been proven to be beneficial, preventing millions of deaths from cardiovascular disease and stroke, and reducing the burden on health services. Many individual countries around the globe have already taken action against reducing population salt intake. These strategies were either led by government, nongovernment organizations, or industry. Keywords: Dietary sodium, Salt, Hypertension, Sodium measurement, Cost-effectiveness.